Enhanced visible-light-response photocatalytic degradation of methylene blue on Fe-loaded BiVO4photocatalyst - Sinaporn Chala (2018)
Pure BiVO 4 and nominal 0.5-5.0 mol% Fe-loaded BiVO 4 samples were synthesized by hydrothermal method. All samples were characterized in order to obtain the correlation between structure and photocatalytic properties by X-ray diffraction, Brunauer, Emmett and Teller, UV-vis diffuse reflectance spectrophotometry, photoluminescence spectroscopy, transmission electron microscopy, X-ray photoelectron spectroscopy and inductively coupled plasma-optical emission spectroscopy. The structure of all samples was single-phase monoclinic scheelite. The absorption spectrum of 5.0 mol% Fe-loaded BiVO 4 shifted to the visible region, suggesting the potential application of this material as a superior visible-light driven photocatalyst in comparison with pure BiVO 4 . Photocatalytic activities of all photocatalyst samples were examined by studying the degradation of methylene blue under visible light irradiation. The results clearly showed that Fe-loaded BiVO 4 sample exhibited remarkably higher activity than pure BiVO 4 . © 2014 Elsevier B.V. All rights reserved.